Zondervan 2018 minister's tax & financial guide : for 2017 tax returns - Busby, Dan; Van Drunen, John; Martin, Michael; Recorded Books, Inc. (Grand Rapids : Zondervan, 2018)
For years, ministers have trusted the Zondervan Minister's Tax and Financial Guide to save them time and money. This easy-to-understand workbook simplifies the tax code and offers dozens of tips to reduce your tax bill. For 2018, the guide includes a line-by-line explanation of the 1040 Form as well as information on recent changes in the tax code. Dan Busby also explains the easy steps you can take now to minimize next year's tax bill. This 2018 edition also includes sound retirement planning helps, compensation planning guidance, and ways to maximize business expense reimbursements. Zondervan 2018 Minister's Tax and Financial Guide is also useful to church treasurers, business administrators, and tax preparers who assist ministers.
Keywords: Clergy -- Taxation -- Law and legislation -- United States; Income tax -- Law and legislation -- United States; RELIGION / Christian Ministry / Pastoral Resources; Religion; Income tax -- Law and legislation; Clergy -- Taxation -- Law and legislation; Religion; United States